EFEKTIVITAS PENERAPAN HUKUMAN DISIPLIN BAGI ANGGOTA KEPOLISIAN - Erianto, Erianto; Fitriati, Fitriati (Program Magister Ilmu Hukum Universitas Ekasakti, 2018)
Law Number 2 Year 2002 on Police and Government regulation Number 2 Year 2003 on Discipline of Members of the Police Force of the Republic of Indonesia is a regulation that must be followed by every member of the Police in performing its functions, duties and authority to realize a professional and accountable Police. Disciplinary punishment with various types of sanctions has been imposed on violators through disciplinary proceedings, but the facts show that violations are increasing every year so disciplinary enforcement has not been effective in deterring members and demonstrating the relatively low level of legal compliance of members of the Polres Pesisir Selatan.